2015
DOI: 10.1093/aob/mcv128
|View full text |Cite
|
Sign up to set email alerts
|

The developmental genetics of biological robustness

Abstract: Studying biological robustness involves focusing on an important property of developmental traits, which is the phenotypic distribution within a population. This is often neglected because the vast majority of developmental biology studies instead focus on population aggregates, such as trait averages. By drawing on findings in animals and yeast, this Viewpoint considers how studies on plant developmental robustness may benefit from strict definitions of what is the developmental system of choice and what is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 96 publications
0
39
0
4
Order By: Relevance
“…The development of the seam cells is canalized to the point of eutely, so that during normal development the balance of asymmetric and symmetric divisions maintains a constant seam cell number (Sulston and Horvitz, ). Variation in the number of seam cells can be used as a metric for phenotypic variation in animals subjected to genetic perturbation in addition to environmental stress (Mestek Boukhibar and Barkoulas, ; Katsanos et al, ). In C. elegans , we find that a number of DnaJs, not limited to ER‐associated chaperones, are involved in canalization.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the seam cells is canalized to the point of eutely, so that during normal development the balance of asymmetric and symmetric divisions maintains a constant seam cell number (Sulston and Horvitz, ). Variation in the number of seam cells can be used as a metric for phenotypic variation in animals subjected to genetic perturbation in addition to environmental stress (Mestek Boukhibar and Barkoulas, ; Katsanos et al, ). In C. elegans , we find that a number of DnaJs, not limited to ER‐associated chaperones, are involved in canalization.…”
Section: Introductionmentioning
confidence: 99%
“…Originally considered to represent a transient, early state of nascent gene duplicates, large scale studies revealed that genetically redundant gene paralogs are widespread and can remain conserved for hundreds of millions of years (Gu et al, 2003;Conant and Wagner, 2004;Tischler et al, 2006;Hsiao and Vitkup, 2008;Vavouri et al, 2008;Hanada et al, 2009). The notable abundance and persistence of genetic redundancy between gene paralogs is hypothesized to be maintained by purifying selection due to the beneficial effect on biological robustness by mitigating the effects of intrinsic, mutational, and environmental variation on organismal development and function (Mestek Boukhibar and Barkoulas, 2016). Moreover, case studies have revealed that ancient DGDs can both maintain partial genetic redundancy for critical developmental patterning junctures in parallel to evolving paralog-specific functions (Bao et al, 2012;Friedrich, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of phenotypic noise (Yvert et al 2013) has been highlighted with the development of experimental technologies measuring single-cell variability (Elowitz et al 2002;Raser and O'Shea 2005;Ohya et al 2015). Recent experimental studies indicate that phenotypic noise affects organismal fitness, is controlled genetically, and is evolvable both in single-cell organisms (Ito et al 2009;Viñuelas et al 2012;Keren et al 2016;Bódi et al 2017;Duveau et al 2018;Reyes et al 2018) and multicellular organisms (Ordas et al 2008;Hill and Mulder 2010;Pelabon et al 2010;Shen et al 2012;Metzger et al 2015;Boukhibar and Barkoulas 2016;Mulder et al 2016).…”
mentioning
confidence: 99%